Derivatives and Default Risk - Sebastian Scholz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
Upstream producers that possess market power, sell forwards with a lengthy duration to regional electricity companies (REC). As part of the liberalization of the electricity market, RECs have been privatized and exposed to a possible bankruptcy threat if spot prices have fallen below their expected value. The downstream firms' expected profit is larger, when it is less likely to be bailed out, the effect on upstream profits is ambiguous while consumers loose. Options are less welfare increasing than forwards, but the difference is minimal. In the presence of bankruptcy, options are the preferred welfare maximizing market instrument.
urn:nbn:de:bvb:19-epub-11317-0
Keywords: D43; G33; G34; G35; 330; Forwards; Options; Default Risk; Market Efficiency; Elektrizität; Rohstoffderivat; Optionsgeschäft; Derivat; Effizienzmarkthypothese; Elektrizitätswirtschaft; Insolvenz; Risiko; Lieferantenmanagement; Oligopol; Wohlfahrtsanalyse; Theorie